Desain Dies Proses Piercing dan Shearing pada Pembuatan Clamping - Irwan Suriaman; Risky Maulana; Choirul Anwar; Jatira; Yadi Heryadi; TB. U. Subekhi; Dede A Rajab (Sekolah Tinggi Teknologi Wastukancana, 2026)
A trolley fabrication company that implements a make-to-order system in the production process. Of the several types of trolley models, one of them is the mesh model trolley where one of the components uses a clamp plate. Where the clamp plate functions to bind one component to another so that the mesh trolley can function more effectively. It is made using a press machine with Punch and Dies. In making clamping, the process used is shearing and piercing. The selection of dies will be based on the practicality of the product manufacturing process, as well as the relatively cheaper cost of making dies. In the manufacturing process of this product, a single compound die will be used. The shearing and piercing processes are only one process, so it can save a lot of time and costs. For this die planning process, the work includes the amount of cutting force, the required machine capacity, clearance, punch dimensions, dies dimensions and supporting tools used. The material used to make clamping is SPCC SD with a thickness of 3 mm. The machine capacity used is 25 tons. The cutting operational force for the shearing process is 62361.6 N, for the piercing hole process is 20267.5 N. So by using a separately made punch contour design, it can make it easier during the maintenanceprocess and the production process can be carried out in bulk.